MULTIKULTURALISME DALAM WACANA ALQURAN - Rusli, Rusli (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: The paper deals with the concept of multiculturalism from the Quranic perspective. It is argued that since the beginning, the Quran recognised and appreciated diversity based on race, religion, culture, and so on. Even, the Quran itself was revealed in the multicultural context. The epistemological basis for multiculturalism in the discourse of the Quran is â€œhuman dignityâ€, from which emerge a set of basic rights that must be respected and protected, which becomes an ethical foundation of multiculturalism. As a consequence of protecting the basic rights, the concept of justice and equality comes to surface. Since human beings are created as sacred and equal, hurting them and their rights is violation to universal humanity. Therefore, to achieve peace, toleration is necessary. To do this task, the strategy of anti-discrimination and prejudice reduction to different groups based on ethnicity, race, culture, and religionâ€”is highly necessary to be established according to local context.Kata Kunci:Â Â Â Â Â  Alquran, multikulturalisme, hak asasi manusia, keadilan, toleransi, dialog